Pemberdayaan UMKM Guna Meningkatkan Produktifitas Usaha Jogjogan Chips (EnyeMilanKu) di Desa Jogjogan, Kecamatan Cisarua, Kabupaten Bogor - Kartini, Tini; Ayun, Mutiara Qurota; Marlina, Dina; Silaningsih, Endang; Yuningsih, Erni; Seran, Gotfridus Goris; Sastrawan, Berry (Journal Of Human And Education (JAHE), 2024)
One of the productive economic efforts that can generate added value and economic value is MSMEs. The role of MSMEs has a significant positive value for the Indonesian economy. The significant growth of MSMEs has given rise to very tight competition. For this reason, there needs to be a commitment from every business actor in improving the right product strategy and innovation to survive in the market. The objectives of this community service are (1) to assist MSMEs in improving product innovation from product flavor and size variants; (2) to increase income and increase business productivity; (3) to create logos, packaging and give product names to MSMEs. Based on observations, it is known that MSMEs have difficulty in marketing their products due to (1) lack of product innovation from flavor and size variants; (2) understanding of calculating the cost of goods sold; (3) logos, packaging that are not attractive enough and giving product names to MSMEs. The results of community service for MSMEs are (1) technical guidance assistance in making product innovations from product flavor and size variants; (2) assistance in knowledge of calculating the cost of goods sold; (3) assistance in creating logos, packaging and giving product names to MSMEs. After this MSME mentoring is carried out, it is hoped that their products will be known to the public and can increase sales productivity and appropriate income.